2012
DOI: 10.1364/ol.37.001691
|View full text |Cite
|
Sign up to set email alerts
|

Compact, highly efficient ytterbium doped bismuthate glass waveguide laser

Abstract: Laser slope efficiencies close to the quantum defect limit and in excess of 78% have been obtained from an ultrafast laser inscribed buried channel waveguide fabricated in a ytterbium-doped bismuthate glass. The simultaneous achievement of low propagation losses and preservation of the fluorescence properties of ytterbium ions is the basis of the outstanding laser performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 10 publications
0
31
0
1
Order By: Relevance
“…In particular, Ytterbium-doped media emitting around 1 micron offer high absorption and emission cross-sections along with a low quantum defect that makes them ideal for high-power direct diode-pumping with a low thermal load. For direct laser written devices Yb-WGLs hold the current records regarding output power (2.35 W [12],) and slope efficiency (79% [13],), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Ytterbium-doped media emitting around 1 micron offer high absorption and emission cross-sections along with a low quantum defect that makes them ideal for high-power direct diode-pumping with a low thermal load. For direct laser written devices Yb-WGLs hold the current records regarding output power (2.35 W [12],) and slope efficiency (79% [13],), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Low insertion loss waveguides with symmetric cross-sections are realised using a multi-scan technique 47 , inscribed with pulse energies∼50nJ. Previously, highly efficient continuous wave lasing was demonstrated from these, with top slope efficiency∼79% 48 . The pump source is a polarisation-maintaining fibercoupled diode laser at 976nm, with 530mW maximum pump power, and an angle cleaved fiber to avoid back re- flections.…”
mentioning
confidence: 99%
“…Both emission bandwidth as well as emission crosssection of 4 I 13/2 / 4 I 15/2 emission transition of Er 3þ ions showed continuous increase with the increase of Bi 2 O 3 contents in glasses ideal for broadband optical signal amplifiers. In addition to this, Ohara et al [12] and Mary et al [13] have recently demonstrated efficient fiber as well as waveguide lasers based on Yb 3þ doped bismuthate glasses.…”
Section: Introductionmentioning
confidence: 95%